Building an Optimal Persistence Model for Novice Arab Minority Teachers by Emotional, School-Organizational and Educational Factors - Zubeidat, Ihab; Dallasheh, Waleed (Journal of Ecohumanism, 2024)
The present study aimed to examine the persistence difficulties of novice teachers from Arab society in relation to various socio-emotional, school-organizational, and educational factors. Another aim of the study was to suggest an appropriate persistence model adapted to novice Arab teachers from Israel. To this end, 319 Israeli novice teachers from Arab society filled out questionnaires on demographics, resilience, organizational commitment, management style, inclusive school, and self-efficacy. The findings indicated significant differences among three levels of persistence difficulty groups in resilience, management style, school inclusion, and self-efficacy. Further post-hoc analysis using Scheffé’s test identified significant differences between specific pairs of groups. Additionally, significant negative relationships were found between novice teachers’ persistence difficulties and their organizational commitment at school, school inclusion, and self-efficacy. Stepwise multiple regression analysis revealed that self-efficacy, school inclusion, resilience, and organizational commitment explained 19.8% of the variance in novice teachers’ persistence difficulties. In conclusion, a targeted support program addressing the unique socio-emotional, school-organizational, and educational training challenges faced by novice Arab teachers in Israel is essential for enhancing their persistence and professional success. Implementing comprehensive and inclusive strategies will not only improve teacher retention but also contribute to a more equitable and effective education system.